Amelogenesis imperfecta: Next-generation sequencing sheds light on Witkop’s classification - Bloch-Zupan, Agnes; Rey, Tristan; Jimenez-Armijo, Alexandra; Kawczynski, Marzena; Kharouf, Naji; , O-Rare consortium; Dure-Molla, Muriel de La; Noirrit, Emmanuelle; Hernandez, Magali; Joseph-Beaudin, Clara; Lopez, Serena; Tardieu, Corinne; et al. (Frontiers in Physiology, 2023)
Amelogenesis imperfecta (AI) is a heterogeneous group of genetic rare diseases disrupting enamel development (Smith et al., 2017). The clinical enamel phenotypes can be described as hypoplastic, hypomineralized or hypomature and serve as a basis, together with the mode of inheritance, to Witkop’s classification (Witkop, 1988). AI can be described in isolation or associated with others symptoms in syndromes. Its occurrence was estimated to range from 1/700 to 1/14000. More than 70 genes have currently been identified as causative. OBJECTIVES: We analyzed using next generation sequencing (NGS GenoDENT panel) a heterogeneous cohort of AI patients in order to determine the molecular etiology of AI and to improve diagnosis and disease management. GenoDENT obtained a 60% diagnostic rate. We reported genetics results for 221 persons divided between 115 AI index cases and their 106 associated relatives from a total of 111 families. From this index cohort, 73% were diagnosed with non-syndromic amelogenesis imperfecta and 27% with syndromic amelogenesis imperfecta. Each individual was classified according to the AI phenotype. Type I hypoplastic AI represented 61 individuals (53 %), Type II hypomature AI affected 31 individuals (27%), Type III hypomineralized AI was diagnosed in 18 individuals (16%) and Type IV hypoplastic-hypomature AI with taurodontism concerned 5 individuals (4%). We validated the genetic diagnosis, with class 4 (likely pathogenic) or class 5 (pathogenic) variants, for 81% of the cohort, and identified candidate variants (variant of uncertain significance or VUS) for 19% of index cases. Among the 151 sequenced variants, 47 are newly reported and classified as class 4 or 5. The most frequently discovered genotypes were associated with MMP20 and FAM83H for isolated AI. FAM20A and LTBP3 genes were the most frequent genes identified for syndromic AI. Patients negative to the panel were resolved with exome sequencing elucidating for example the gene involved ie ACP4 or digenic inheritance. NGS GenoDENT panel is a validated and cost-efficient technique offering new perspectives to understand underlying molecular mechanisms of AI. Discovering variants in genes involved in syndromic AI (CNNM4, WDR72, FAM20A…) transformed patient overall care. Unravelling the genetic basis of AI sheds light on Witkop’s AI classification.